The Role of Social Networks in Shaping the Image of the State during a Full-Scale War - Yemets, Valentyna; Moroz, Andrii (Mediaforum : Analytics, Forecasts, Information Management, 2023)
The country’s foreign policy activity involves decision-making, building coordination and communication with using information and communication technologies, and in the first head with the aim to influence the formation of foreign public opinion regarding the creation of a positive image of the state at the international level. The image of the state acts as a strategic resource of national interests on the geopolitical map of the world, presents its geographical, economic, historical and cultural features and is oriented towards international actors: states, transnational corporations, international and regional organizations and the world public. The most powerful tools for forming the image of the state are the information and communication technologies of social networks, which are characterized by the instantaneous transmission of information from the original source to a wide audience. At the same time, the global information space began to be actively used as a field for conducting informational and psychological operations and information wars with the aim of pressure on opponents. And social networks have turned into a tool for creating both a positive and a negative image of the state.